Real‐Time Observation of Superstructure‐Dependent DNA Origami Digestion by DNase I Using High‐Speed Atomic Force Microscopy. (11th October 2019) - Ramakrishnan, Saminathan; Shen, Boxuan; Kostiainen, Mauri A.; Grundmeier, Guido; Keller, Adrian; Linko, Veikko
Abstract: DNA nanostructures have emerged as intriguing tools for numerous biomedical applications. However, in many of those applications and most notably in drug delivery, their stability and function may be compromised by the biological media. A particularly important issue for medical applications is their interaction with proteins such as endonucleases, which may degrade the well‐defined nanoscale shapes. Herein, fundamental insights into this interaction are provided by monitoring DNase I digestion of four structurally distinct DNA origami nanostructures (DONs) in real time and at a single‐structure level by using high‐speed atomic force microscopy. The effect of the solid–liquid interface on DON digestion is also assessed by comparison with experiments in bulk solution. It is shown that DON digestion is strongly dependent on its superstructure and flexibility and on the local topology of the individual structure. Abstract : Beyond the fold : High‐speed atomic force microscopy and electrophoretic mobility shift assays reveal that DNA origami is digested by DNase I in a superstructure‐dependent way. The cleavage profiles are also different at the immobilized and suspended states of DNA origami.